Budget impact analysis of sarilumab for the treatment of rheumatoid arthritis in patients with an inadequate response to conventional synthetic DMARD or TNF inhibitor therapies - Ferrufino CP; Munakata J; Wei W; Proudfoot C; Kuznik A; Boklage SH; Chen C (Dove Medical Press, 2018)
Cheryl P Ferrufino,1 Julie Munakata,1 Wenhui Wei,2 Clare Proudfoot,3 Andreas Kuznik,4 Susan H Boklage,4 Chieh-I Chen4 1IQVIA, Fairfax, VA, USA; 2Sanofi, Bridgewater, NJ, USA; 3Sanofi, Guildford, UK; 4Regeneron Pharmaceuticals, Inc., Tarrytown, NY, USA Objective: To estimate the 5-year budget impact (BI) on a US health plan of introducing sarilumab – a human immunoglobulin G1 anti-IL-6 receptor α monoclonal antibody – as combination treatment with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) or monotherapy in patients with moderate-to-severe rheumatoid arthritis (RA).Methods: BI analysis was conducted from a commercial payer perspective. Treatment-eligible populations included adult patients with moderate-to-severe RA and inadequate response (IR) to csDMARDs or tumor necrosis factor (TNF)-α inhibitors-IR. All licensed biologic treatments recommended by the American College of Rheumatology guidelines were included.Results: For a hypothetical plan of one million members, 409 csDMARD-IR and 345 TNF-IR patients were annually eligible for combination therapy and 226 csDMARD and TNF-IR patients for monotherapy with sarilumab. Based on 2018 US direct treatment costs, the introduction of sarilumab was estimated to save $526,424, $322,637 and $264,306 over 5 years for csDMARD-IR combination therapy patients, TNF-IR combination therapy patients, and csDMARD-IR/TNF-IR monotherapy patients, respectively. As sarilumab absorbed a greater market share over the horizon, annual savings increased from years 1 to 5, $28,610 (–0.14%) to $194,646 (–0.83%) in csDMARD-IR, $16,986 (–0.11%) to $120,893 (–0.67%) in TNF-IR, and $14,256 (–0.13%) to $98,040 (–0.79%) in monotherapy. One-way sensitivity analyses revealed that the model was most sensitive to variations in sarilumab adherence.Conclusion: Total cost savings of introducing sarilumab to a health-care plan accrued from years 1 to 5, attributable to the lower treatment cost, stable dosing paradigm, and price parity for the two available doses (150 and 200 mg every 2 weeks) compared with alternative biologic DMARDs that have substantial variability in dose titration/schedules. Keywords: treatment costs, disease-modifying anti-rheumatic drug, IL-6 inhibitor